PENGARUH KOMPETENSI, INDEPENDENSI DAN PENGALAMAN TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI (Studi Pada Auditor Kantor Akuntan Publik di Jawa Tengah dan DIY) - Novi Anggraeni, 14.05.52.0107; Himmawan, Arief (Students' Journal of Accounting and Banking, 2018)
Audit quality is the quality of the work of an auditor who is shown with a reliable report of the results of the examination. Audit quality is influenced by various factors including competence, independence, experience and auditor ethics. This study aims to examine the influence of competence, independence and experience on audit quality with auditor ethics as a moderation variable. The population in this study are all auditors who work in Public Accounting Firm of Central Java and Yogyakarta Special Region DIY. Sampling was done by using convinience sampling method and obtained a sample of 65 respondents. The method of collecting primary data was conducted through survey method using questionnaire. The data obtained were analyzed using the test of absolute difference value to test the effect of the moderation variable through SPSS 19.0. The results of this study indicate that competence has a positive and significant effect on audit quality, independence has no significant effect on audit quality and experience has no significant effect on audit quality. The ethics of the auditor does not moderate the influence of competence, independence, experience on audit quality. Keywords: competence, independence, experience, auditor ethics and audit quality